Pelatihan Pengolahan dan Pemanfaatan Limbah Bulu Ayam Menjadi Panel Dinding Ramah Lingkungan Di Desa Borisallo Kecamatan Parangloe Kabupaten Gowa - Faharuddin, Ansarullah; Nashrah Arsyad; Gusti Hardyanti (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2022)
Chicken aging is a food that is consumed by almost every community, because the price is quite affordable and delicious. This results in considerable feather waste and if not processed properly can result in environmental pollution. Feather waste is produced on average 6% of the weight, so processing technology or creativity is needed in its utilization. For the development of science and technology, research has been conducted on the processing of chicken feather waste into building materials in the form of wall panels. The results of the research are expected to meet the needs of building materials and become an alternative wall panel material. Its abundant availability provides new references in science in the field of architecture and information on environmentally friendly materials. In 2021, the PKM team has provided education about the use of chicken feathers as an environmentally friendly panel material to Borisallo Village residents. As a follow-up, the PKM activity implementation team again carried out activities in the form of training in processing chicken feather waste into panels. The results of these activities can increase the knowledge and skills of Borisallo Village residents in processing and producing wall panels from chicken feather-based materials.